2017
DOI: 10.1016/j.nucengdes.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Interface tracking simulations of bubbly flows in PWR relevant geometries

Abstract: The advances in high performance computing (HPC) have allowed direct numerical simulation (DNS) approach coupled with interface tracking methods (ITM) to perform high fidelity simulations of turbulent bubbly flows in various complex geometries. In this work, we have chosen the geometry of the pressurized water reactor (PWR) core subchannel to perform a set of interface tracking simulations (ITS) with fully resolved liquid turbulence. The presented research utilizes a massively parallel finite-element based cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…More recently, a slug-to-churn flow regime transition study reported favorable agreement between PHASTA results and the existing experimental and analytical results for complex two-phase flow regimes (Zimmer and Bolotnov, 2019). The two-phase flow simulation capability can also be extended to even larger engineering problems, such as nuclear reactor subchannels (Fang et al, 2017(Fang et al, , 2018(Fang et al, , 2020.…”
Section: Flow Solver and Interface Capturing Approachmentioning
confidence: 64%
“…More recently, a slug-to-churn flow regime transition study reported favorable agreement between PHASTA results and the existing experimental and analytical results for complex two-phase flow regimes (Zimmer and Bolotnov, 2019). The two-phase flow simulation capability can also be extended to even larger engineering problems, such as nuclear reactor subchannels (Fang et al, 2017(Fang et al, , 2018(Fang et al, , 2020.…”
Section: Flow Solver and Interface Capturing Approachmentioning
confidence: 64%
“…Data from probes in each loci from all quadrants at corresponding wall distance locations are averaged, which yields the mean wall distance function trend for the selected lateral plane (for further details on data averaging, see [35]). The inlet profile was compared with the DNS results for flow between parallel plates by Lee et al [52] and flow in a sub-channel, with similar geometrical specifications as the present work, by Fang et al [60]. Considering the canonical linear Log law of the wall, Figure 5 shows the normalized principal Reynolds stresses, = 〈 〉/ and normalized turbulent kinetic energy (TKE), = 0.5 〈 ′〉/ , compared with the trends obtained from Lee et al [52] and Fang et al [60].…”
Section: Verification Of Inlet Turbulent Flow Featuresmentioning
confidence: 92%
“…More geometric details are listed in Table 3. Although the investigated Reynolds number is only roughly a sixth of that under the realistic PWR flow condition [5], it is still much higher than what one can find in the literature for DNS studies on reactor coolant flow [9]. In DNS, the grid spacing must be sufficiently fine to capture the small scales of interest.…”
Section: Simulation Setupmentioning
confidence: 97%
“…As an indispensable requirement for DNS solver, the excellent scaling performance of PHASTA has already been demonstrated in massively parallel simulations (up to 786,432 cores) [4]. PHASTA can be also utilized in two-phase flow simulations by incorporating the level set method to track the gas-liquid interface [5]. For the details of code FTC3D please refer to previous publication [6].…”
Section: Description Of Numerical Codesmentioning
confidence: 99%